Peroxiredoxin 6 Peroxidase and Ca2+-Independent Phospholipase A2 Activities Are Essential to Support Male-Mouse Fertility - Edrian Bumanlag; Eleonora Scarlata; Cristian O'Flaherty (MDPI AG, 2022)
Human infertility is an important health problem that affects one in six couples worldwide. Half of these cases are due to male infertility. Oxidative stress is a common culprit of male infertility, promoting lipid peroxidation and the oxidation of proteins and DNA in spermatozoa, thereby impairing motility, capacitation and fertilization. Peroxiredoxin 6 (PRDX6) possesses peroxidase and Ca2+-independent-phospholipase-A2 (iPLA2) activities that scavenge ROS and repair oxidized sperm membranes, respectively. PRDX6 protects spermatozoa against oxidative stress. Infertile men's spermatozoa have impaired motility, elevated lipid peroxidation levels and DNA damage due to low PRDX6 levels. A lack of PRDX6 is associated with male-mouse infertility. Here, we determined the impact of the absence of PRDX6 peroxidase or iPLA2 activities on male-mouse fertility. Two-month-old male C57Bl6/J (wild-type), Prdx6−/−, C47S and D140A knock-in (peroxidase- and iPLA2-deficient, respectively) male mice were challenged with an in vivo oxidative stress triggered by tert-butyl hydroperoxide (t-BHP). C47S and D140A males produced smaller litters compared to wild-type controls. The t-BHP treatment promoted a lower number of pups, high levels of lipid peroxidation, tyrosine nitration, and DNA oxidation in all mutant spermatozoa compared to wild-type controls. All mutant spermatozoa had impaired capacitation and motility. In summary, both PRDX6 peroxidase and iPLA2 activities are essential to support male-mouse fertility.